2021
DOI: 10.1002/pssb.202100263
|View full text |Cite
|
Sign up to set email alerts
|

Growth Dynamics and Electron Reflectivity in Ultrathin Films of Chiral Heptahelicene on Metal (100) Surfaces Studied by Spin‐Polarized Low Energy Electron Microscopy

Abstract: Molecular layers on surfaces have been widely used to study effects occurring at molecule/substrate interfaces. By controlling kinetic and thermodynamic conditions during the assembly of nano-objects, in particular molecules and atoms, various patterns of self-assembled, metalcoordinated or covalently linked structures have been obtained by careful selection of the components and surface symmetry. [1] Not only are these patterns interesting for their topologies, they also were found to induce interesting inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The most obvious difference may be the fact that, while Naaman has studied adsorption from solution phases, we have studied adsorption from a collisionless UHV environment. A recent study performed by Ernst [36] and also conducted under UHV conditions reported the absence of the CISS effect or spin selective transport through a homochiral helicene film. Under UHV conditions, the Asp is sublimated from the glass evaporator at T=4384ptK ${T=438\ K}$ and travels ballistically to the surface without experiencing any collisions with other species or a barrier to adsorption at the surface.…”
Section: Discussionmentioning
confidence: 96%
“…The most obvious difference may be the fact that, while Naaman has studied adsorption from solution phases, we have studied adsorption from a collisionless UHV environment. A recent study performed by Ernst [36] and also conducted under UHV conditions reported the absence of the CISS effect or spin selective transport through a homochiral helicene film. Under UHV conditions, the Asp is sublimated from the glass evaporator at T=4384ptK ${T=438\ K}$ and travels ballistically to the surface without experiencing any collisions with other species or a barrier to adsorption at the surface.…”
Section: Discussionmentioning
confidence: 96%
“…In recent studies of chiral molecules on ferromagnetic Ni(100), neither enantiomeric separation nor differences in adsorption kinetics between magnetic domains were observed. [24,25] Here, we report enantiospecific adsorption of heptahelicene, a chiral helical polyaromatic molecule, on ferromagnetic singlecrystal cobalt surfaces in ultrahigh vacuum by means of spinpolarized scanning tunneling microscopy (SP-STM). Lateral enantioselection onto domains of opposite out-of-plane magnetization occurs in a transient physisorbed precursor state before final chemisorption.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies of chiral molecules on ferromagnetic Ni(100), neither enantiomeric separation nor differences in adsorption kinetics between magnetic domains were observed. [ 24,25 ]…”
Section: Introductionmentioning
confidence: 99%